Analysis of Factors Influencing Purchase Decision Via Tiktok Shop Application (A Case Study of Muslim Gen Z in Malang City) - Restu Putra, Dimas; Khusnia Anggraini, Ika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The background of this study is based on the increasing trend of online shopping and the dominance of social media as a digital marketing channel. This study aims to analyze the influence of price perception, video marketing content, emotional motives, rational motives, and halal awareness on the purchasing decisions of Gen Z Muslims in Malang City through the TikTok Shop application. The focus of this study is Gen Z Muslim customers who frequently use TikTok Shop. The results show that only emotional motives from the five variables tested have a significant influence on their purchasing decisions; price perception, video marketing content, rational motives, and knowledge about halal have no influence. In short, religious values, price, promotions, and rationality are not the main factors when Gen Z Muslims choose goods.